Rancang Bangun Game Edukasi untuk Anak Autis dengan Level yang Disesuaikan dengan Tingkat Autis Anak menggunakan Sistem Pakar - Robi Naufal Kaosar, - (2021)
Educational games for autistic children are learning media specifically for autistic children, both in terms of themes, appearance, curriculum, and so on. So that the game can be played by the autistic child, it is necessary to adjust the difficulty level of the game with the child's level of autism. To determine the type of developmental disorder in children, an expert system can be used. The research method used in this research is the research and development method, or commonly called Research and Development (R&D). The material applied to this educational game is reading and counting material for autistic children. Users of educational games that implement this expert system are SDLB students in grades 2-3 and SDLB teachers.